Close Collaboration with Parents-Implementation and effectiveness - Ahlqvist-Björkroth, Sari (Wiley-Blackwell, 2025)
Aim: There has been a need to develop programs to facilitate family-centered care. This paper describes the content of a program called Close Collaboration with Parents, its implementation, and research on its effectiveness.
Methods: The program is a systematic training with a focus on staff communication and observation skills and skills to support parenting. The primary implementation strategy is mentoring. Staff engage in bedside practices and reflections with mentors covering all four phases of the program. The effects of this unit-wide program have been evaluated using a pre-post study design, a qualitative study design, and a register-based study design.
Results: The program has been successfully implemented in 26 units so far. Our research has shown that the training benefits infants, parents, staff, and healthcare organisations. Specifically, family-centered care practices improved after the program, the parents' presence and parent-infant skin-to-skin contact increased, infant growth improved and the length of hospital stays shortened. The mothers' depressive symptoms decreased in the long term.
Conclusion: We have described an educational program for the multidisciplinary staff of a neonatal intensive care unit, Close Collaboration with Parents. The program has changed hospital care cultures for the benefit of infants, parents, staff, and even the healthcare organisation.